Knowledge, attitudes and reported practices of general practitioners related to adult female patients with urinary incontinence in greater Johannesburg - Padayachey, Moganambal (My University, 2010)
BACKGROUND There is an extraordinary common medical condition that affects millions of people, mostly women. It is associated with high levels of disability, discomfort and loss of productivity. People seldom talk about it and suffer in silence and have a fear of being ridiculed or embarrassed. It is not breast cancer, nor osteoporosis, nor heart disease nor is it depression. It is urinary incontinence – the loss of bladder control, which affects the lives of millions of people globally. General Practitioners (GP‟s) do not have a good knowledge about the topic and are therefore not managing Urinary Incontinence (UI) appropriately. AIM To assess the knowledge, attitudes and reported practices of general practitioners related to adult female patients with urinary incontinence in Greater Johannesburg. OBJECTIVES To determine the demographics of the respondents belonging to the various Independent Practitioner Associations (IPA's). Variables include age, sex, year qualified, postgraduate qualifications, and the number of years in clinical practice. To determine the demographics of the respondents practice. Variables include, age distribution, gender distribution, and the number of patients seen with urinary incontinence per month. To determine the knowledge of the respondents regarding urinary incontinence in adult females. Variables include prevalence, aetiology, types of urinary incontinence, associated risk factors and reversible factors. v To determine the attitudes of the respondents regarding urinary incontinence in adult females. Variables include feelings of empathy, frustration, etc. To determine the management of the respondents regarding urinary incontinence in adult females. Variables include access of referral facilities, screening, examination, investigation, and medication. METHODS The study was done amongst the Independent Practitioner Associations in the greater Johannesburg area. A questionnaire was administered to GP‟s attending IPA meetings, data was collected with regards to the demographics of the GPs and their practices as well as the knowledge, attitudes and reported practices of the GPs. RESULTS The response rate cannot be calculated as the number of GPs who attended the IPA meetings is not known. One hundred and thirteen respondents met the inclusion criteria for the study. The data was collected over a 10-month period during 2006. Males accounted for 76 (68.5%) and females for 35 (31.5%) of all respondents. Two (1.8%) respondents had three postgraduate qualifications, 11 (9.7%) respondents had two postgraduate qualifications and 38 (33.6%) respondents had one postgraduate qualification. The prevalence of patients with UI was higher amongst female respondents, 33 (97.1%) as compared to male respondents 67 (88.2%). Feelings of empathy was experienced by 94 (88.7%) respondents and 81 (81%) respondents would never avoided the discussion about UI with patients. Most respondents rated their knowledge on aetiology 82 (78.1%), diagnosis 79 (73.8%), investigation 58 (54.2%) and management 58 (54.7%) as good and very good.
Keywords: urinary incontinence; adult females